Marketing strategy based on personality types of the Myers-Briggs Type Indicator - Feng Qingyu; Zhang Yuhan (SHS Web of Conferences)
This study explores the relationship between personality types, specifically Extraversion (E) and Introversion (I) as classified by the Myers-Briggs Type Indicator (MBTI). Marketing strategy based on personality types of the Myers-Briggs Type Indicator and their implications for designing targeted marketing strategies based on personality types. By analyzing the distinct characteristics of extroverts, who thrive in social environments and seek stimulating interactions, against Introverts, who prefer reflective engagement and deeper connections, the research identifies specific preferences and behaviors that inform effective marketing approaches. Through word frequency analysis of social media language, the study highlights how Extraverts are more likely to engage with dynamic, interactive content, while Introverts favor meaningful, emotionally resonant narratives. The findings emphasize the importance of tailoring marketing messages and channels to align with these personality-driven preferences, ultimately guiding marketers toward creating more personalized and impactful campaigns that resonate authentically with diverse consumer segments. This research contributes to a deeper understanding of personality-driven marketing and underscores the necessity for businesses to adapt their strategies to the distinct needs of different personality types.